IMPLEMENTASI PERATURAN MENTERI PERHUBUNGAN NOMOR 63 TAHUN 2019 TENTANG STANDAR PELAYANAN MINIMUM ORANG DENGAN KERETA API PADA PT KAI DAOP 4 KOTA SEMARANG (Studi Penelitian Untuk Penyandang Disabilitas Fisik) - Veronica Bella Anggraeni PutriMarlita; Puji Astuti (Journal of Politic and Government Studies, 2026)
Inclusive public transportation services are an important part of fulfilling the right to mobility for all citizens, including people with disabilities. Through the Regulation of the Minister of Transportation Number 63 of 2019, the government stipulates the Minimum Service Standard (SPM) for transporting people by train as a standard for providing safe, comfortable, and accessible services. However, practice in the field still shows a gap between provisions and implementation, including in PT. KAI DAOP 4 Semarang, which has the characteristics of a heritage station, is also a type A station with a fairly high number of passengers. This study aims to analyze the implementation of SPM at Semarang Tawang Station and Semarang Poncol Station, especially for people with physical disabilities, and identify supporting and inhibiting factors. Using the George C. Edwards III policy implementation model, this study examines four variables, namely communication, resources, disposition, and bureaucratic structure. This study uses qualitative methods conducted through interviews, field observations, and documentation, with resource persons station management officers, wheelchair users, and companions of people with disabilities. The results of the study show that internal communication runs systematically through multi-stage socialization, but information to users with disabilities is not evenly distributed. Human resources are considered quite adequate, while some physical facilities are still limited. The disposition of the officers shows a positive commitment, but it is not consistent in all service lines. The bureaucratic structure has clear SOPs, but cross-unit coordination and the involvement of people with disabilities in service evaluation still need to be strengthened.